The Conventional Nature of Non-MHC-Restricted T Cells - Lepore, Marco; Mori, Lucia; De Libero, Gennaro (Frontiers in Immunology, 2018)
The definition “unconventional T cells” identifies T lymphocytes that recognize non-peptide antigens presented by monomorphic antigen-presenting molecules. Two cell populations recognize lipid antigens and small metabolites presented by CD1 and MR1 molecules, respectively. A third cell population expressing the TCR Vγ9Vδ2 is stimulated by small phosphorylated metabolites. In the recent past, we have learnt a lot about the selection, tissue distribution, gene transcription programs, mode of expansion after antigen recognition, and persistence of these cells. These studies depict their functions in immune homeostasis and diseases. Current investigations are revealing that unconventional T cells include distinct sub-populations, which display unexpected similarities to classical MHC-restricted T cells in terms of TCR repertoire diversity, antigen specificity variety, functional heterogeneity, and naïve-to-memory differentiation dynamic. This review discusses the latest findings with a particular emphasis on these T cells, which appear to be more conventional than previously appreciated, and with the perspective of using CD1 and MR1-restricted T cells in vaccination and immunotherapy.